(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Caralluma attenuata Wight belonging to family Asclepidaceae is a succulent herb. In the present study In-vitro anti diabetic properties were determined. Determination of glucose adsorption capacity, Effect of Caralluma attenuata extract on In-vitro glucose diffusion and Glucose uptake by yeast cells were used to determine the in-vitro anti diabetic properties of Caralluma attenuata. The results reveal that the alcoholic extract of Caralluma attenuata possess a significant anti diabetic properties In-vitro models it is observed that increase in concentration of alcoholic extract of Caralluma attenuata are able to produce increase in anti-diabetic properties.